Contaminant interaction and remediation in soil microcosms and pilot-scale studies - Herbath, Y. (Cranfield University, 2003)
The contamination of soil, groundwater and ultimately potable water sources, is a quantifiable risk associated with the sub-surface release of cable oil into the environment. This research has provided the National Grid Transco (NGT) with an evaluation of the feasibility of biological systems as a means of re mediating soil and groundwater contaminated with cable oil. This has been achieved through treatability studies undertaken at three levels of process sophistication; laboratory-scales micro-cosms, a pilot-study to develop full-scale design criteria and a full-scale pilot-study under semi-controlled field conditions. The full-scale pilot-scale study was undertaken together with a simple temporal and spatial model of oil distribution through two contrasting soil blocks. Experimental data obtained in this thesis has shown, for the first time that anaerobic degradation processes are able to offer an effective alternative to aerobic in situ bioremediation for cable oil. Each level of process in this three-phase study has demonstrated anaerobic soil organisms capable of survival on cable oil and mineral salts ~lone. Sulphate reducing micro-organisms are also suggested as playing an important role in the degradation process. Biodegradation of the cable oil of up to 41 % was achieved, in some cases reducing the concentration to below 50ppm threshold required by the Dutch Intervention Values (1994). The study of pollutant migration found that the temporal and spatial distribution of cable oil is specific to soil type and is influenced by the soil structure, particle size distribution and water suction potential. The extent of oil migration in both soils is a function of the volume of cable oil present and is time dependent. The significant outcome of this work is that prior to this study, there have been no reports of higher alkylbenzenes being degraded anaerobically. Consequently, monitored natural attenuation may now be considered by NGT as a feasible remediation option under certain conditions, providing an acceptable, non-intrusive technique for sites contaminated with cable oil.